A nested case-control study on the association of gut virome in early pregnancy and gestational diabetes mellitus - Wu, Xinrui; Liu, Xinpeng; Xu, Wenbo; Chen, Wenhui; Zhong, Zixin; Tan, Hongzhuan; Xiang, Tianyu (Frontiers in Microbiology, 2024)
BackgroundRecent studies have increasingly shown the connection between gut microbiome and gestational diabetes mellitus (GDM). However, no studies have explored the relationship between the gut virome and GDM, and the underlying mechanism remains unknown.MethodsWe performed a nested case-control study within a follow-up cohort, enrolling 51 patients with GDM and 51 healthy controls. Shotgun metagenomics sequencing was used to explore gut virome profiles during early pregnancy.ResultsDiversity analysis revealed no difference in the overall gut virome composition between two groups, however, we found greater abundance of Escherichia phage SH2026Stx1 (Q = 0.23), Enterobacteria phage mEp043 c-1 (Q = 0.21), crAssphage cr50_1 (Q = 0.21), Enterobacteria phage phi80 (Q = 0.21), and Escherichia phage HK106 (Q = 0.23) in GDM patients. Cross-kingdom correlation analysis showed the negative correlation between the gut bacterium Eubacterium eligens and three bacteriophages (Escherichia phage SH2026Stx1, Enterobacteria phage mEp043 c-1, and Escherichia phage HK106) in GDM group (r < 0, P < 0.05). Based on gut microbial features and clinical indicators, we constructed a new prediction model using random forest method for GDM with good predictive performance (AUC of 0.893, 95% CI: 0.736 ∼ 0.990).ConclusionThis study is the first to investigate the relationship between the gut virome and GDM as well as the cross-kingdom correlation between gut viruses and bacteria in GDM. Our findings could enhance strategies for preventing and treating GDM from the perspective of gut microbiome, offering valuable insights into its pathogenesis.